2021
DOI: 10.1186/s12889-021-10941-3
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and future self-rated health: a prospective cohort study

Abstract: Background Negative life events (re) occurring during childhood is often described as adverse childhood experiences (ACEs) and may have long-lasting negative effects on health. Previous studies on the association between ACEs and self-rated health (SRH) have primarily been focusing on chronic diseases in elderly, non-Scandinavian populations using a cross-sectional design. The aim of the study was to examine the associations between ACEs and SRH in early adulthood and to investigate if disadvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It is intended that prospective research on ACEs in association with other mental health problems will be pursued in this population. The Young HUNT 3 study will then be the largest prospective, population-based, cross-sectional Scandinavian study focusing on ACEs [33]. Because of the used population, the results of this study can be generalized in western world countries as Norway.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…It is intended that prospective research on ACEs in association with other mental health problems will be pursued in this population. The Young HUNT 3 study will then be the largest prospective, population-based, cross-sectional Scandinavian study focusing on ACEs [33]. Because of the used population, the results of this study can be generalized in western world countries as Norway.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In this prospective cohort study of ACE exposure, ACEs were tracked at varying age groups and SRH values were also recorded for comparison. There was a proportional increase in ACE and SRH scores [32], suggesting a substantial degree of correlation. A better understanding of ACEs may lead to more accurate approaches for predicting future health effects of ACEs and, Contemporary Developments and Perspectives in International Health Security -Volume 3 therefore, may help in the development of earlier and more effective interventions.…”
Section: Adverse Childhood Experiences: Focus On Long-term Sequelaementioning
confidence: 85%
“…Another 2021 study published in BMC Public Health showed a correlation between ACEs and self-rated health (SRH) in young adults [32]. In this prospective cohort study of ACE exposure, ACEs were tracked at varying age groups and SRH values were also recorded for comparison.…”
Section: Adverse Childhood Experiences: Focus On Long-term Sequelaementioning
confidence: 99%
“…We also found that the greater the number of ACEs reported by individuals, the lower the likelihood of HIV testing, indicating there was a dose-response relationship. The effects of ACEs on health-hazardous behaviours and health status can be cumulative or multiplicative (Bellis et al, 2014;Jahn et al, 2021). Alcala et al (Alcala et al, 2018) in their study of the effects of ACEs on cancer screening found that each increase in ACEs decreased the odds of individuals performing PSA tests, Pap tests, and colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 99%